A new genus and two new species of Luzarinae cricket from the Atlantic Forest of Northeast Brazil (Orthoptera, Grylloidea) - Souza-Dias, Pedro G. B.; Desutter-Grandcolas, Laure (Zootaxa, 2014)
A new genus and two new species of Luzarinae crickets (Grylloidea, Phalangopsidae) are described from the Atlantic Forest of Northeast Brazil. Marcgraviella muriciensis Souza-Dias n. gen., n. sp. and M. christianae Desutter-Grandcolas & Souza-Dias n. gen., n. sp. are described using characters of morphology and male genitalia. The new genus is characterized by male genitalia singularities, presenting elongated and inflatable pseudepiphallic parameres, which lies in vertical or almost vertical position, and long and tubular pseudepiphallic arms associated to phallic glands. We provide a discussion about the morphology of male genitalia and the function of the phallic glands and pseudepiphallic arms in Marcgraviella n. gen. and related taxa. An identification key for Marcgraviella n. gen. and related genera is proposed. These genera, which bear phallic glands, are placed in the newly named group, the Aracambiae.